Determining the Effects of Molar Ratio, Alkali Catalyst Concentration and Temperature on Transesterification of Jatropha Oil - Amish P. Vyas; Jaswant L. Verma; Late Nandula Subrahmanyam (Progress in Chemical Science Research Vol. 3, 2022)
Among novel methods to carry out transesterification of the Jatropha oil, Ultrasound Assisted Transesterification is one of the best techniques in terms of reduction in process time and stages of the biodiesel process. On the conversion of Jatropha oil to biodiesel, the effects of process factors including the catalyst loading, the methanol to oil molar ratio, reaction temperature, and reaction duration were examined. Under the circumstances of 50°C, a methanol to oil molar ratio of 9:1, a reaction time of 30 min, and a catalyst quantity (catalyst/oil) of 1% wt%, the conversion was over 93 percent. This research presents a kinetic investigation of the transesterification of Jatropha oil using ultrasonic assisted synthesis and makes a case for its applicability for first order reaction. The derived rate equation is also shown.